Standar Penerapan Wisata Halal Bagi Pelaku Industri Pariwisata di Kota Bandung - Bernik, Merita; R Indika, Deru; Komala Dewi, Rita (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
Bandung is one of the halal tourist destinations in Indonesia. With the increasingly rapid growth of cafes and restaurants, the competition is getting tougher. One of the highlights is whether the cafÃ© and restaurant are halal certified. This becomes very important because Indonesia is one of the largest Islamic countries in the World. It is proper if halal is the main concern. The business people do not understand and realize the importance of fulfilling the halal standard set by the government. So through this community service will be carried out socialization regarding required halal tourism. The method used in this study is the Deplat Pastisipatif which is conducting activities in the form of providing counseling and guidance on halal tourism and halal standardization on SMEs in the culinary sector in the city of Bandung, especially the Jatinangor region. Counseling was carried out by inviting from the tourism , youth and sport agency and also the MUI. Culinary business begin to understand halal standardization and the importance of having halal certification. There is still a need for assistance to be able to implement halal tourism properly.